THE EFFECT OF HALAL LABEL ON FOOD PURCHASING DECISIONS IN LHOKSEUMAWE CITY - Fuadi; Aida; Hamdani; Husni Pasarela (PT. Radja Intercontinental Publishing, 2024)
This research aims to examine the influence of the Halal Label on Siomay Purchasing Decisions in Public Understanding in Lhokseumawe City. The data used in this research is primary data from 50 respondents. The method used to analyze the relationship between variables is simple linear regression analysis using the Statistical Package for the Social Sciences (SPSS) software version 25. The results of the study show that the halal label does not have significant influence on the decision to purchase dumplings in Lhokseumawe City. This implies that consumers' understanding of the use of the halal label influences the decision to purchase dumplings, with a t value that is less than the t table, namely 1.091<1.677, and a significance level of 0.281.